2012
DOI: 10.2135/cropsci2011.05.0246
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gains in Grain Yield and Physiological Traits of Winter Wheat in Shandong Province, China, from 1969 to 2006

Abstract: Knowledge on the changes in yield potential and associated physiological traits is essential for understanding the main yield‐limiting factors and guiding future breeding strategies. Our objective was to identify physiological traits associated with genetic gains in grain yield of winter wheat (Triticum aestivum L.) in Shandong province, China. Thirteen milestone cultivars and two advanced lines released from 1969 to 2006 were examined over 3 yr at Tai'an during 2006 to 2009. The genetic gain in grain yield wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
131
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 41 publications
33
131
5
1
Order By: Relevance
“…Our results under conventional tillage ( Fig. 1(C)) are coincident with those of other authors (Green et al 2012;Lopes et al 2012;Matus et al 2012;Xiao et al 2012;Sanchez-García et al 2013), where a significant genetic progress was achieved during the…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Our results under conventional tillage ( Fig. 1(C)) are coincident with those of other authors (Green et al 2012;Lopes et al 2012;Matus et al 2012;Xiao et al 2012;Sanchez-García et al 2013), where a significant genetic progress was achieved during the…”
supporting
confidence: 92%
“…A general tendency of reduction in the wheat plant height was found by several authors as a result of breeding programs (Zhou et al 2007;Xiao et al 2012). However, an increased partitioning through additional reduction in plant height is not likely, as comparative studies indicate that optimal plant heights have already been achieved (Mustaoea and Saulescu 2011;Zheng et al 2011;Lopes et al 2012).…”
Section: Cereal Research Communications 42 2014mentioning
confidence: 86%
See 1 more Smart Citation
“…Broad genotypic variations were found among the tested wheat genotypes for the grain yield, CTD (Balota et al, 2008;Li et al, 2012), LSR Lopes and Reynolds, 2012), SPAD (Lopes and Reynolds, 2012;Xiao et al, 2012), Fm and Fv (Araus et al, 1998;, Fv/Fm (Sayar et al, 2008;Kumar et al, 2012), and leaf and grain ash content (Merah et al, 2001;Zhu et al, 2009) in both experiments, as has been reported by other authors. Grain yield is very sensitive to drought stress and it remarkably decreased under the late drought conditions.…”
Section: Genotypic Variations In the Physiological Traits And Their Rsupporting
confidence: 84%
“…In wheat (Triticum aestivum L.), chlorophyll content is positively correlated with photosynthetic rate (Evans, 1983). Leaf chlorophyll (measured by extraction and quantification of pigment content or with optical chlorophyll meters) is increasingly emphasized as an indicator for photosynthetic capacity and its stability during senescence (the 'stay green' phenotype) under both stress and non-stress conditions, and therefore for yield in wheat (Reynolds et al, 1994;Araus et al, 2008;Parry et al, 2011;Xiao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%